Effects of inulin and canistel addition in the physical characteristics of fat-reduced processed cheese (Research, Society and Development, 2020)
Processed cheese is characterized as a homogeneous mixture, formed mainly by protein and fat, which directly influence its texture. When using fat substitute ingredients, such as hydrocolloids, it is important to evaluate their effect on the physical properties of the final product. The inulin was used as a fat substitute, and canistel, an exotic fruit, as a natural dye and source of bioactive compounds, with the aim of developing processed cheese reduced in fat by 50% (R50) and 100% (R100) and evaluate the effect of this reduction on rheological and texture properties compared to a Standard (S) formulation. Carotenoid content, color, texture and dynamic rheological properties (frequency and temperature scanning) were evaluated. Fat-reduced processed cheeses showed a yellowish color, an increase of more than 10x in the carotenoid content and hardness value reduction in relation to the S. All formulations demonstrated the viscoelastic behavior and the elastic properties were predominant throughout the temperature sweep, mainly for the R50, showing greater stability. The use of inulin and canistel in a product with reduced fat has potential for the food industry, since the first maintains the physical characteristics of the product while the second, increases the content of bioactive compounds and gives natural coloring.